(untitled) (Scientia Agricola, 2014)
'Bordô' grapevines (Vitis labrusca) have great relevance to viticulture due to the quality they can impart to wines and juices. However, this cultivar has high variation in yield, ranging from 6 to 11 t ha-1. The use of clones with superior genetic potential related to scions currently marketed may increase crop profitability and revitalize its cultivation. The aim of this study was to evaluate the agronomical responses of twelve clones of the Bordô cultivar selected over a period of 15 years according to yield and quality. The vineyard was planted in 2008. Grape plants were grafted onto '1103 Paulsen' rootstock and trained on vertical shoot positioning. The agronomical evaluations, performed in the 2011, 2012 and 2013 seasons, covered the duration of their phenological cycles, shoot growth, yield per plant, estimated total yield and physicochemical characteristics. Differences were found between clones in terms of phenology, yield components, and berry composition. Clone 6 had the lowest yield, averaging 5.0 t ha-1 whereas clone 13 was the most productive with 14.9 t ha-1. Based on the most productive vineyards in the region (10.8 t ha-1), the adoption of more productive clones can generate an increase in yield of around 38 %.